(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To identify the predisposing factors for both invasive and non-invasive Aspergillus rhinosinusitis and to understand the relationship of these factors with Aspergillus infection of the paranasal sinuses. Study Design: Retrospective analytic study Place and Duration of Study: This study was carried out in Department of ENT Unit 1; Mayo Hospital affiliated with King Edward Medical University, Lahore. It spanned over a period of 18 months from January 2008 to June 2009. Material and Method: A total of 29 patients diagnosed to have Aspergillus rhinosinusitis were included in the study. A properly designed, structured, validated and tested questionnaire was used for data collection .Categorical variables included were gender, diabetes mellitus, tuberculosis, asthma, contact with birds and animals. Chi-square test was used to see the association between final diagnosis and the variables tested. Results: In our study the average age of patients with non-invasive disease was 28.22 ± 11. 875 years and with invasive disease was 29.18 ± 18.132 years. The ratio of male patients was almost twice that of females. 11 (37.93 %) patients had indolent invasive Aspergillus rhinosinusitis and 18 (62.7 %) had non-invasive Aspergillus rhinosinusitis. Final diagnosis was independent of gender (p=0.149), Diabetes (p=0.379), Asthma (p=0.864), contacts with birds (p=1.00) and animals (p=0.466). Interestingly, 5 (45.45 %) out of 11 patients with invasive disease had tuberculosis and only 1 (5.55 %) out of 18 patients with non-invasive disease had tuberculosis (p=0.018). Conclusion: Aspergillus rhinosinusitis is a disease of the young adults. No specific predisposing factor could be identified in the causation of non-invasive Aspergillus rhinosinusitis. Tuberculosis was the only positive factor identified in invasive indolent Aspergillus infection of the paranasal sinuses.